Late Preterm and Term Birth: Neonatal Hyperbilirubinemia and Birth Model. (3rd July 2016) - Ozdemirci, Safak; Kut, Altug; Salgur, Funda
ABSTRACT: Aim : To evaluate the mode of delivery's influence on development of neonatal hyperbilirubinemia in term or near term infants. Methods : The hyperbilirubinemic neonates were divided into two groups according to their mode of delivery (i.e., vaginal or cesarean). The birth weight and gestational age at the time of birth, the age of the neonates in days, and the serum levels of bilirubin of the neonates at the time of hyperbilirubinemia were compared from the date of hospitalization until treatment, based on the birth model. Results : 288 were fulfilled the inclusion criteria during the neonatal period. The vaginal delivery group consisted of 157 infants (16.8%) with hyperbilirubinemia, whereas the cesarean group included 131 (22.6%) infants with hyperbilirubinemia. Neonates in the cesarean group had a significantly higher rate of hyperbilirubinemia ( p = 0.01). Conclusion : This study revealed that compared with vaginal births, cesarean births led to higher rates of neonatal hyperbilirubinemia.